2022
DOI: 10.3389/fimmu.2022.827865
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiome and Bile Acid Metabolism Induced the Activation of CXCR5+ CD4+ T Follicular Helper Cells to Participate in Neuromyelitis Optica Spectrum Disorder Recurrence

Abstract: From the perspective of the role of T follicular helper (Tfh) cells in the destruction of tolerance in disease progression, more attention has been paid to their role in autoimmunity. To address the role of Tfh cells in neuromyelitis optica spectrum disorder (NMOSD) recurrence, serum C-X-C motif ligand 13 (CXCL13) levels reflect the effects of the Tfh cells on B-cell-mediated humoral immunity. We evaluated the immunobiology of the CXCR5+CD4+ Tfh cells in 46 patients with NMOSD, including 37 patients with NMOSD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…In addition, Tfh cells were found to contribute to the pathophysiology in an NMOSD mouse model, and Tfh cell depletion via abrogating ICOS/ICOS-L signaling ameliorated astrocytopathy (Yick et al, 2023). Tfh cells were also found positively correlated with severity (Monteiro et al, 2019; and relapse (Cheng et al, 2022;Fan et al, 2016;Zhao et al, 2017) in NMOSD patients.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition, Tfh cells were found to contribute to the pathophysiology in an NMOSD mouse model, and Tfh cell depletion via abrogating ICOS/ICOS-L signaling ameliorated astrocytopathy (Yick et al, 2023). Tfh cells were also found positively correlated with severity (Monteiro et al, 2019; and relapse (Cheng et al, 2022;Fan et al, 2016;Zhao et al, 2017) in NMOSD patients.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, Tfh cells were found to contribute to the pathophysiology in an NMOSD mouse model, and Tfh cell depletion via abrogating ICOS/ICOS‐L signaling ameliorated astrocytopathy (Yick et al., 2023 ). Tfh cells were also found positively correlated with severity (Monteiro et al., 2019 ; Yang et al., 2021 ) and relapse (Cheng et al., 2022 ; Fan et al., 2016 ; Zhao et al., 2017 ) in NMOSD patients. Fan and colleagues concurrently confirmed the positive correlation of percentages of CCR7‐ and CCR7‐ICOS + memory Tfh cells with AQP4‐IgG level (Fan et al., 2016 ).…”
Section: Discussionmentioning
confidence: 94%
“…[84] Variations of several gut microorganisms, especially Vagococcus and Anaerobiospirillum spp., and their metabolites (e.g., bile acids), correlated with NMOSD recurrence through CXCL13-induced activation of the CXCR5+ CD4+ follicular T helper cell pathway. [85] Gut microbiota and MG…”
Section: ≥2mentioning
confidence: 99%
“…In addition, a study of sigmoid mucosal biopsies from NMOSD patients proposed that mucosal microbiota imbalance and inflammatory cell activation allowed pathogens to cross the damaged intestinal barrier and participate in the pathogenesis of NMOSD [84] . Variations of several gut microorganisms, especially Vagococcus and Anaerobiospirillum spp., and their metabolites (e.g., bile acids), correlated with NMOSD recurrence through CXCL13-induced activation of the CXCR5+ CD4+ follicular T helper cell pathway [85] …”
Section: Gut Microbiota and Neurological Diseasesmentioning
confidence: 99%
“…( Shan et al., 2017 ) found that the percentages of CXCR5+CD4+ Tfh cells in OA patients were significantly higher than that in the healthy control group. Interestingly, a novel insight showed that the activation of CXCR5+CD4+ Tfh cells could be induced by gut microbiota and bile acid metabolism ( Cheng et al., 2022 ). Segmented filamentous bacteria, a gut-residing specie, has been demonstrated to drive autoimmune arthritis via Th17 cells ( Wu et al., 2010 ), which can be accumulated in the synovial fluid and synovial tissue of OA patients ( Chabaud et al., 1999 ; Qi et al., 2016 ).…”
Section: Gut Microbiota Is Involved In the Development Of Oa Through ...mentioning
confidence: 99%